2002
DOI: 10.1073/pnas.042496899
|View full text |Cite
|
Sign up to set email alerts
|

α-Helical stabilization by side chain shielding of backbone hydrogen bonds

Abstract: We study atomic models of the thermodynamics of the structural transition of peptides that form ␣-helices. The effect of sequence variation on ␣-helix formation for alanine-rich peptides, Ac-Ala21-methyl amide (A21) and Ac-A5 (AAARA)3A-methyl amide (Fs peptide), is investigated by atomic simulation studies of the thermodynamics of the helix-coil transition in explicit water. The simulations show that the guanidinium group in the Arg side chains in the Fs peptide interacts with the carbonyl group four amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
470
5
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 442 publications
(518 citation statements)
references
References 46 publications
41
470
5
2
Order By: Relevance
“…Another structural study of alanine dipeptide using 13 C NMR 49 confirmed the presence of PP II conformation, but also suggests that a mixture of PP II and α R is more likely in water. The dominance of PP II in trialanine was reiterated by two-dimensional vibrational spectroscopy studies of Woutersen & Hamm 50,51 and later modified by the same authors to include around 20% of α R apart from PP II 52 .…”
Section: Force Field Validationmentioning
confidence: 95%
See 4 more Smart Citations
“…Another structural study of alanine dipeptide using 13 C NMR 49 confirmed the presence of PP II conformation, but also suggests that a mixture of PP II and α R is more likely in water. The dominance of PP II in trialanine was reiterated by two-dimensional vibrational spectroscopy studies of Woutersen & Hamm 50,51 and later modified by the same authors to include around 20% of α R apart from PP II 52 .…”
Section: Force Field Validationmentioning
confidence: 95%
“…All molecular dynamics simulations for Gly 3 and Ala 3 tetrapeptides were carried out with the sander module in AMBER8 7 using several different force fields as discussed in the main text: ff94 5 , ff99 11 , Garcia's modification of ff94 13 with C-N-C α -C and N-C α -C-N terms zeroed (denoted ff94gs in the text), Pande's modified ff99 19 with C-N-C α -C term replaced by the one from ff94 (denoted ff99ϕ), ff03 24 (as present in AMBER8 distribution) and ff99SB developed as described above. The time step was 2 fs, and all bonds involving hydrogen were constrained by SHAKE with a tolerance of 10 −4 Å. Glycine and alanine tetrapeptide systems were solvated by approximately 520 TIP3P 33 water molecules in a periodic box.…”
Section: Simulations In Explicit Watermentioning
confidence: 99%
See 3 more Smart Citations